Revisiting Avicenna's (AD 980-1037) anatomical concepts of the musculoskeletal and peripheral nervous systems in the Canon of medicine - Mazengenya, Pedzisai (Array, 2018)
Avicenna, as he is known in the West, was a famous Persian Muslim physician and influential philosopher-scientist of the medieval Islamic world. He wrote and compiled the Canon of Medicine text, a book which was adopted as the main text of medicine at the most Persian and Western universities. The book consists of basic medical sciences, applied clinical sciences and pharmacology. In the current study, we present an analysis of the anatomy of the musculoskeletal and peripheral nervous systems as viewed by Avicenna in the Canon of Medicine, and compare them with the relevant modern literature.